2008
DOI: 10.1152/ajpcell.00232.2008
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 promotes intestinal epithelial restitution by increasing Ca2+ influx through interaction with phospholipase C-γ1 after wounding

Abstract: Intestinal mucosal restitution occurs as a consequence of epithelial cell migration and reseals superficial wounds after injury. This rapid reepithelialization is mediated in part by a phospholipase C-gamma1 (PLC-gamma1)-induced Ca(2+) signaling, but the exact mechanism underlying such signaling and its regulation remains elusive. The small GTP-binding protein Rac1 functions as a pivotal regulator of several signaling networks and plays an important role in regulating cell motility. The current study tests the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 56 publications
8
73
0
Order By: Relevance
“…Not finding that MAPK pathways are involved in the activation of TonEBP/ OREBP by Rac1, we turned our attention to PLC-γ1 based on reports that PLC-γ1 contributes to activation of TonEBP/ OREBP (3) and that Rac1 can activate PLC-γ1 (16,17). We compared the effect of Rac1 in PLC-γ1-null MEFs to its effect in the same cells in which PLC-γ1 is reconstituted (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not finding that MAPK pathways are involved in the activation of TonEBP/ OREBP by Rac1, we turned our attention to PLC-γ1 based on reports that PLC-γ1 contributes to activation of TonEBP/ OREBP (3) and that Rac1 can activate PLC-γ1 (16,17). We compared the effect of Rac1 in PLC-γ1-null MEFs to its effect in the same cells in which PLC-γ1 is reconstituted (18).…”
Section: Resultsmentioning
confidence: 99%
“…Having found that regulation of TonEBP/OREBP by Rac1 is not mediated by MKK3 and p38, we tested whether mediation is via PLC-γ1, which contributes to regulation of TonEBP/OREBP (3), interacts directly with Rac1 (16,25), and can be a downstream target of Rac1 (16,17). In addition, Rac1 often acts in combination with PLC-γ1 to regulate cellular signaling events (16,25,26). In the present study, we find that caRac1 and dominant-negative Rac1 do not affect TonEBP/ OREBP transcriptional activity in PLC-γ1-null MEFs unless PLC-γ1 is reconstituted (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3A, 4A). Rac1 activation increases Ca 2+ influx in epithelial cells (36), and mast cells activate PKCs, MAPKs, and NF-kB/AP-1 signal pathways (28). PKC regulates NF-kB-dependent transcription (59).…”
Section: Discussionmentioning
confidence: 99%
“…The 8-oxo-dG is a Rac1/2 and cdc42 inhibitor (33-35) Rac1 increases Ca 2+ influx in epithelial cells (36). The 8-oxo-dG pretreatment inhibited Rho activation (Fig.…”
Section: Effects Of a Rac Inhibitor Or Camentioning
confidence: 97%
“…Flasks were incubated at 37°C in a humidified atmosphere of 90% air-10% CO 2, and passages 15-20 were used in experiments. IEC-6 cells at passages 15-20 exhibit a stable phenotype (9,42).…”
Section: Methodsmentioning
confidence: 99%